Estudio de la composición y estructura del bosque andino localizado en Potrero Grande, Chipaque (Colombia) (2020)
The forests of the Andes are large reservoirs of biodiversity and endemism and constitute a priority land ecoregion worldwide. However, the loss and degradation of habitats caused by conflicts of use has generated irreparable consequences for the quality of the supply of resources and services of these ecosystems, being one of the main threats to their conservation. To counteract this situation, an eventual alternative lies in studying the ecological succession of secondary forests in order to know the ecology and assembly of plant communities, and thus, favor decision-making regarding the restoration of these ecosystems. In this study, the composition and structure of the secondary vegetation of the Andean Forest located in the municipality of Chipaque was analyzed. Two plots of 0.1ha and one of 0.05ha were established in homogeneous vegetation fragments; physiognomic variables were recorded for seedling, saplings and poles. There were 523 individuals distributed in 48 species, 36 genera and 25 families; the diversity indices showed three different plant communities with low dominance of species and high diversity of taxa. The densities of individuals for diameter classes and heights showed a tendency to positive asymmetric distribution, showing an active regeneration; the Value of Significance Index indicated the species Clusia multiflora and Centronia brachycera with greater ecological representativeness. The floristic heterogeneity found provides strategic scientific knowledge to explore different alternatives of propagation and introduction of native species in restoration processes in degraded areas of the region.